2017
DOI: 10.1038/ng.3760
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study implicates immune activation of multiple integrin genes in inflammatory bowel disease

Abstract: Genetic association studies have identified 215 risk loci for inflammatory bowel disease 1–8, which have revealed fundamental aspects of its molecular biology. We performed a genome-wide association study of 25,305 individuals, and meta-analyzed with published summary statistics, yielding a total sample size of 59,957 subjects. We identified 25 new loci, three of which contain integrin genes that encode proteins in pathways identified as important therapeutic targets in inflammatory bowel disease. The associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
716
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,119 publications
(826 citation statements)
references
References 59 publications
20
716
3
2
Order By: Relevance
“…They are in line with the observation that most risk genes leading to the onset of IBD are involved in the pathways of innate immunity rather than adaptive immunity 8. Macrophages may play a more important role in IBD pathophysiology as compared with the T-cells compartment.…”
supporting
confidence: 85%
“…They are in line with the observation that most risk genes leading to the onset of IBD are involved in the pathways of innate immunity rather than adaptive immunity 8. Macrophages may play a more important role in IBD pathophysiology as compared with the T-cells compartment.…”
supporting
confidence: 85%
“…ICAM1 was recently identified as a candidate gene at an IBD susceptibility locus, with upregulated gene expression associated with the disease-risk variant. 33 ICAM1 is a transmembrane adhesion protein commonly expressed by vascular endothelium and leukocytes. Binding of ICAM1 to the LFA1 receptor on T cells facilitates and stabilizes cell-cell interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Altered expression of RNASET2 , both increased and decreased, is associated with various diseases, including cancers 25–27 and autoimmune diseases, 29, 40, 43, 44 suggesting a role for RNASET2 in host immune responses. RNASET2 expression is downregulated and likely involved in the pathogenesis of colorectal cancer, 33 melanoma, 19 anaplastic large cell lymphoma 34 and non-Hodgkin lymphoma. 27 In human ovarian cancer overexpression of RNASET2 is associated with tumor suppression and is believed to modulate tumor micro-environment cross-talk through recruitment of monocyte/macrophages to the tumor itself.…”
Section: Discussionmentioning
confidence: 99%
“…This means that some SNPs will only affect pathogenicity on, for example, inflammation or during infection. These context-specific eQTLs are now used in search of causative genes in GWAS 15. A recent study has identified eQTLs in ileal biopsies from patients in different stages of CD (healthy, complication-free disease and disease progression with stricturing or penetrating disease).…”
Section: Regulatory Information Creates Novel Insight In Cell Types Amentioning
confidence: 99%